Crecimiento pro-pobre en Colombia: 2002-2011 (2013)
Abstract: This research proposes a broader vision of welfare growth and its impact on poverty and inequality for which addresses the theoretical framework based on the growth pro-poor proposed Kawany & Son (2008) who implement a measure that relates these three elements from this analysis is performed in Colombia in 2002-2011 comprised level departmental setting the various typologies of pro-poor growth and poverty trends measured by the gap indicator Foster, Greer and Thorbecke poverty and implement policies